On Site Evaluation of a Tubular Microbial Fuel Cell Using an Anion Exchange Membrane for Sewage Water Treatment - Sugioka, Mari; Yoshida, Naoko; Iida, Kazuki (Frontiers in Energy Research, 2019)
This study evaluated the performance of a tubular microbial fuel cell (MFC) having a core of air-chamber wrapped with an anion exchange membrane in sewage wastewater treatment. Three MFCs were vertically assembled into one module and floated in sewage water channels before and after treatments in the primary sedimentation tank. The two MFC-modules exhibited nearly similar electricity production in the range of 1.3–5.7 Wh·m−3-MFC while the bottom MFCs (60–90 cm) showed a decrease in electricity compared with the top (0–30 cm) and the middle MFCs (30–60 cm) due to the water leakage into air-cathode. One MFC module was then evaluated for its chemical oxygen demand (COD) removal efficiency with two external resistances of 27 and 3Ω in a chemostat reactor (MFC:reactor = 1:5, v/v) using three hydraulic retention times (HRTs), i.e., 3, 6, and 12 h. The best COD removal efficiency (COD-REMFC), 54 ± 14%, and BOD removal efficiency, 37 ± 17%, were observed with a resistance of 3Ω and a 12 h HRT, which resulted in 3.8 ± 2.0 A·m−3 of current recovery and 15 ± 7.5% of Coulombic efficiency. The electricity generation efficiency (EGEMFC) was the best with a resistance of 27Ω and a 12 h HRT, accounting for 0.19 ± 0.12 kWh·kg-COD−1 with a 17 ± 6.4% COD-REMFC and 0.65 ± 0.10 Wh·m−3 electricity production. Based on calculations using the COD-REMFC and EGEMFC, the integration of MFC treatments prior to aeration can reduce wastewater treatment electricity consumption by 55%.